Biology of Maconellicoccus hirsutus (Hemiptera: Pseudococcidae) on Hibiscus rosa-sinensis - Marcelo Negrini; Elisangela Gomes Fidelis de Morais; José Cola Zanuncio (Agro@mbiente On-line)
Maconellicoccus hirsutus Green, 1908 (Hemiptera: Pseudococcidae) is an introduced pest that threatens fruit and ornamental plant production in Brazil. Reported in Brazil for the first time in 2010, in the state of Roraima, M. hirsutus, has spread rapidly to other regions of the country. The objective of this study was to investigate the biology of M. hirsutus on Hibiscus rosa-sinensis L. (Malvaceae) leaves in laboratory conditions with climatic parameters similar to those of the Brazilian North and Northeast (27 ± 1 °C, 60 ± 10% relative humidity and 12 hours light and 12 hours dark). Eighty M. hirsutus nymphs were individualized on rooted H. rosa-sinensis leaves and their survival, mortality, sex ratio, and egg numbers per female emerged were recorded. Maconellicoccus hirsutus can have up to nine generations per year, taking 6.5 days to double its population size. The female numbers of this pest are about three times higher than those for its male counterparts, with 98 eggs per female and 97% viability. The survival curve of the species is type I, that is, mortality rates are higher in adulthood. Maconellicoccus hirsutus, especially, a pest of fruit trees and ornamental plants, presents great potential for population growth in Brazilian tropical conditions.